(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In medical care, patient satisfaction is a key indicator of the quality of care. Many studies have agreed on the fact that measuring patient satisfaction is a useful tool for determining the effectiveness of health care delivery and the quality of medical care provided. Hence, present study was aimed to determine impact of consultant’s performance with special reference to retention and patient satisfaction. A hospital-based cross-sectional study was conducted in 30 large hospital based out in Mumbai Pune on 950 samples of Consultants Administrators. Data were gathered through exit interviews of patients after obtaining their written informed consent. A predesigned and pretested questionnaire on patient satisfaction patient satisfaction questionnaire was used as a study tool. In clinical variables, treatment effectiveness was found to be significantly associated with the satisfaction score (P = .002). The study found that overall patients were highly satisfied with the consultant’s performance medical services provided by the health facility. Furthermore, the study finds that treatment effectiveness has a more significant effect on patients’ satisfaction compared with other factors.